Permainan Papan Sebagai Media Peningkatan Kesadaran Generasi Z Terhadap Pelestarian Artefak Majapahit - Claudia Gabriella Zefanya (VisArt: Jurnal Seni Rupa dan Design, 2025)
The Majapahit Kingdom left a wide range of artifacts that represent the height of its civilization and serve as important sources for understanding Indonesian culture and identity. However, Generation Z’s interest in Majapahit history remains relatively low, as history education is often delivered through conventional methods that feel distant and unengaging. In contrast, younger learners tend to prefer interactive learning media that encourage active participation. This study proposes the design of an educational board game themed around the preservation of Majapahit artifacts as an alternative learning medium. A board game is chosen for its ability to foster face-to-face interaction, encourage collaboration, and create an enjoyable learning experience. The game design applies fundamental board game principles, including mechanics, narrative, and visual elements, to effectively convey historical content. The research employs a qualitative descriptive method. Data collection is conducted through interviews with expert informants, observation of existing history-themed board games, and a literature review on Majapahit history and game-based learning. By integrating educational and entertainment elements, this board game is expected to increase Generation Z’s awareness of the importance of preserving Majapahit historical artifacts while making history learning more relevant and engaging.